Bilateral proximal delta phalanges of hand: a rare case report with review of literature - Kocherla, Keerthi; Kocherla, Prasada Rao; Kocherla, Vasantha Kumari (International Journal of Research in Medical Sciences, 2017)
Delta phalanx or longitudinal bracketed epiphysis is a rare congenital anomaly that affects phalanges in the hand more commonly than toes. It results from a defective secondary ossification that extends longitudinally along the diaphysis and brackets the diaphysis and metaphysis, causing restricted longitudinal growth and resultant angular deformities. Although rare, longitudinal epiphyseal bracket most commonly manifests in the hands as clinodactyly and in the feet as hallux varus. We report a case of 18 year old male patient with isolated bilateral multiple proximal delta phalanges of hand.